Fair compromise in a morally complex world : the allocation of greenhouse gas emission permits between industriaIised and developing countries - Müller, B (Oxford Institute for Energy Studies, 2001)
A fair amount of thought has gone into analysing the perplexing and thorny issues of equity brought about by changes in global climate. Many insightful studies have been published, not least ‘The Complex Elements of Global Fairness’ by Eileen Claussen and Lisa McNeiIly.’ Following their lead, the subject of this note is the moral complexity of climate change - or rather, how to deal with it in a fair and constructive manner. Anyone vaguely familiar with the multilateral climate negotiations will be aware of one specific equity dispute: the question of how to allocate emission quotas (‘assigned amounts’) to the Parties of the UN Framework Convention on Climate Change. While at Kyoto a consensus did emerge on how reduction targets should be distributed amongst industrialised countries - namely at roughly the same percentage relative to their 1990 emission levels’ - there is no agreement as to what a fair worldwide distribution of quotas would or should be. Apart from ‘Grandfathering’ - implicitly espoused by many industrialised country voices who phrase the problem in terns of adopting ‘(meaningful) emission reduction targets’ (Box 1) - the alternative most often cited is an allocation in proportion to population size (‘Per Capita’). In Section II of this note, these two antithetical positions are used to illustrate the ‘Preference Score’ method which, as it were, ‘synthesises’ incompatible proposals in certain morally complex situations into a fair compromise solution.